Rabbani's Character in Social Media: A Study of the Relevance of Al-Qur'an Meme's Instagram Mubadalah.id with Interpretations of Mufasir Nusantara - Eko Zulfikar; Almunadi Almunadi; Abdul Kher (Jurnal Semiotika Quran, 2023)
This article aims to examine the idea of ​​Instagram Mubadalah.id about the character of Rabbani in the Qur’an. In the post that was uploaded in the form of a meme on its website, Mubadalah.id seems to have contributed thoughts about the character of Rabbani that men and women must have. This is interesting to study further, considering that Mubadalah.id is an Instagram social media that actively posts issues around Islam, especially those related to gender. By using qualitative methods and a virtual ethnographic approach, this article concludes that Mubadalah.id’s Instagram provides the idea of ​​nine Rabbani characters based on verses of the Koran which are packaged in the form of memes, namely: having faith in Allah, always doing good deeds, protecting oneself from lust for the world, intertwin hablun minan-nas, have commendable morals, do not oppress women, are aware of their potential, are aware of slander within themselves, and behave in rahmatan lil ‘alamin. The nine characters of Rabbani in the Qur'an offered by Mubadalah.id are very relevant to the interpretation of Mufasir Nusantara against the verses which are used as a benchmark to designate the character of Rabbani. Therefore, the nine Rabbani characters need to be applied in Indonesian social life to achieve a better life.